The Relationship between Principal Self-Efficacy and Organizational Citizenship Behavior of Teachers - Alshaikh, Abdulaziz M.; Bond, John B. (International Dialogues on Education Journal, 2020)
Self-efficacy and organizational citizenship behaviors in schools are critical to understanding interactions between principals and teachers. The main purpose of this research is to look for the relationship between principals’ self-efficacy (PSE) and organizational citizenship behavior (OCB) of teachers. Theoretically, self-efficacy is rooted in constructivism, and, particularly, in social cognitive theory, which is grounded in the work of Bandura. OCB, according to Organ, Podsakoff, and MacKenzie (2006), is defined as “individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and in the aggregate promotes the efficient and effective functioning of the organization” (p. 3).Williams (1988) asserted that OCB is composed of two dimensions: benefits to the individual and benefits to the organization. Interestingly, there is no study, thus far, that addresses the connection between PSE and the OCB of teachers.